Impact of Total Quality Management Practices on Quality Performance: A Case Study on Armament Manufacturing Industry - Berhane, Hagos; Maganti, Pramila Devi (Asian Journal of Engineering and Applied Technology, 2018)
Total quality management (TQM) has been widely considered as the strategic, tactical and operational tool in the quality management research field. It is one of the most applied and well accepted approaches for business excellence besides continuous quality improvement, six sigma, just-in-time, and supply chain management approaches. This study investigated impact of TQM practices on quality performance in an armament manufacturing industry in Ethiopia. The quantitative approach and the survey method of collecting data were used. The five point Likert scale structured questionnaire was administered through the face-to-face method of collecting data. 340 questionnaires were randomly distributed to employees who are working in different factories in the two armament manufacturing industry. Eight factors related to TQM practices were initially selected as independent variables viz., leadership, customer focus, continuous improvement, employee involvement, training and education, supplier management, strategic quality planning, information analysis, and quality performance as dependent variable in the proposed model. Raw data was analysed with the help with SPSS software (version – 20). Mean, standard deviation, exploratory factor analyses, correlation, and multiple regression analyses were used to find the impact of TQM practices on quality performance. The results of this study supported the model proposed (R2 = 0.378, F = 36.292, p = 0.000). This study has shown that only three (viz., leadership, customer focus, and information analysis) of TQM practices significantly (p < 0.05) have positive impact on quality performance. It is recommended that industry should continue to implement TQM practices with all variables to improve quality performance. Industry should improve continuous improvement, employee involvement, training and education, supplier management, strategic quality planning more to overcome the barriers that prevent effective implementation of TQM practices.